Подземные гидротехнические сооружения: учебник для вузов - Мостков В. М. Владимир Михайлович; Орлов В. А. Виктор Алексеевич; Степанов П. Д. Петр Дмитриевич; Хечинов Ю. Е. Юрий Евгеньевич (Москва, Высшая школа, 1986)
Авт. указаны на обороте тит. л.